MicroRNAs and the regulation of cell death. - Xu, P.; Guo, M.; Hay, B.A. (Trends in Genetics, 2004)
Programmed cell death, or apoptosis, is ubiquitous, both during development and in the adult. Many components of the evolutionarily conserved machinery that brings about and regulates cell death have been identified, and all of these are proteins. However, in the past three years it has become clear that roughly 1% of predicted genes in animals encode small noncoding RNAs known as microRNAs, which regulate gene function. Here we review the recent identification of microRNA cell death regulators in Drosophila, hints that such regulators are also likely to exist in mammals, and more generally the approaches and tools that are now available to probe roles for noncoding RNAs in the control of cell death.